Nursing Care in the Home Environment of a 76-Year-Old Female Patient With Chronic Myocardial Failure After Implanted Cardiostimulator - Ryś, Bogusława; Wątroba, Kinga; Bąk, Ewelina; Kostka, Julia (Quality in Sport, 2024)
Chronic heart failure is one of the diseases of affluence It relatively more often affects the elderly, as well as those who suffer from cardiovascular diseases. The theoretical part of the paper contains information on chronic myocardial insufficiency enriched with an artificial pacemaker. In the practical part, a case report of a 76-year-old female patient with chronic myocardial failure after an implanted pacemaker was presented.